ANALYSIS ON THE APPLICATION AND BENEFIT OF FIELD TRIP TO KEBUN RAYA BOGOR ON ECOLOGY SUBJECT IN BIOLOGY EDUCATION STUDY PROGRAM ACADEMIC YEAR 2016/2017 - Yani, Indri (Journal of Humanities and Social Studies, 2018)
The aim of this research is to find out the application and benefit of field trip to Kebun Raya Bogor on Ecology subject in Biology Education Program, FKIP Unpak Bogor.This research is conducted at Kebun Raya Bogor on January during academic year of 2017. Population of this research is students of fourth semester Biology Education Study Program, FKIP Unpak Bogor who attend field trip on ecology subject.Descriptive method is used in this research to describe and analyze the advantages and the application of field trip to Kebun Raya Bogor on ecology subject. Instrument used in this research is questionnaire. Based on the data analysis and the research result it can be said that the application of field trip on ecology subject shows good impact. The successfulness of this field trip is because all students involve in the activity and follow the procedure as it was written on the manual. The benefit of field trip is to prove theory that students learn in the classroom.